SPILLOVER SPASIAL NEGATIF PERTUMBUHAN EKONOMI ANTAR KABUPATEN/KOTA DI PROVINSI JAWA TIMUR - Hani Laksono; Ernan Rustiadi; Hermanto Siregar (TATALOKA, 2018)
Various studies have been conducted to conceive the factors of regional economic growth and its nature in order to obtain the right formulation of regional development policy. The main aim of this research is exploring the spatial influence of economic growth in East Java Province. The result of Lagrange Multiplier test shows that the regencies/cities economic growth affects each other in the long term. Parameters estimation on spatial lag model shows that the spatial influence of economic growth inter regencies/cities is negative. These indicate that development activities in East Java Province have not been get synergistic yet.